Answer:
![\boxed{x = -2~~and~~ y = -4}](https://img.qammunity.org/2021/formulas/mathematics/high-school/395ytvxk2m9lsle68wvn20pkv3yx6aes1v.png)
Explanation:
-2x + 2y = -4 (times 3) -6x + 6y = -12
3x + 3y = -18 (times 2) 6x + 6y = -36
.
-6x + 6y = -12
6x + 6y = -36 +
12y = -48
![y = (-48)/(12)](https://img.qammunity.org/2021/formulas/mathematics/high-school/b7ockpxbgtrogvfpiyei1gqmysb9jipul0.png)
y = -4
.
Substitute the value of y to the one of equations
-2x + 2(-4) = -4
-2x - 8 = -4
-2x = -4 + 8
-2x = 4
![x = (4)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/d0flxtn4fsviz2m2yfwqphnizjztndhiwg.png)
x = -2